Cell elasticity is an important indicator of the metastatic phenotype of melanoma cells. Issue 11 (10th October 2014) - Sarna, Michal; Zadlo, Andrzej; Hermanowicz, Pawel; Madeja, Zbigniew; Burda, Kvetoslava; Sarna, Tadeusz
Abstract The relationship between melanin pigmentation and metastatic phenotype of melanoma cells is an intricate issue, which needs to be unambiguously determined to fully understand the process of metastasis of malignant melanoma. Despite significant research efforts undertaken to solve this problem, the outcomes are far from being satisfying. Importantly, none of the proposed explanations takes into consideration biophysical aspects of the phenomenon such as cell elasticity. Recently, we have demonstrated that melanin granules dramatically modify elastic properties of pigmented melanoma cells. This prompted us to examine the mechanical effects of melanosomes on the transmigration abilities of melanoma cells. Here, we show for the first time that melanin granules inhibit transmigration abilities of melanoma cells in a number of granules dependent manner. Moreover, we demonstrate that the inhibitory effect of melanosomes is mechanical in nature. Results obtained in this study demonstrate that cell elasticity may play a key role in the efficiency of melanoma cells spread in vivo. Our findings may also contribute to better understanding of the process of metastasis of malignant melanoma.